North of the Colour Line: Sleeping Car Porters and the Battle Against Jim Crow on Canadian Rails, 1880-1920 - Mathieu, Sarah-Jane (Saje) (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2001)
Abstract This paper analyses the evolution of Jim Crow employment patterns in the Canadian railway industry from the 1880s to World War I. It presents race as acentral organizing principle in employers' decision to hire black railwaymen for their sleeping and dining car departments. Canadian railway managers actively sought out African American, West Indian, and African Canadian labour, believing that they constituted an easily manipulated group of workers. White railroaders fought the introduction of black employees, arguing that they undermined white manhood and railway unionism. Trade union leaders demanded and won a racialized division of the workforce, locking black workers into low-waged service position when they had initially enjoyed a broader range of employment options. In effect, white railway trade unionists and their employers embraced segregation as a rational model for peaceful working conditions. Black railroaders, on the other hand, resisted the encroachment of segregationist policies by forming their own union, the Order of Sleeping Car Porters. They pressured for change by exposing the scope of Jim Crow practices in the railway industry and trade unionism.